First-line checkpoint inhibitors for wild-type advanced non-small-cell cancer: a pair-wise and network meta-analysis. (25th January 2019) - Wang, Xiao-Jian; Lin, Jia-Zhou; Yu, Shu-Han; Wu, Sheng-Xi; Luo, He-San; Du, Ze-Sen; Li, Xu-Yuan
Aim: To estimate efficacy of checkpoint inhibitors and rank treatment effects in non-small-cell lung cancer.Materials & methods: Prospective randomized trials were included. p-score was used to rank treatment effects.Results: A total of nine trials were identified, involving 5504 patients and three checkpoint inhibitors. Pembrolizumab plus chemotherapy had the highest p-score of 0.95 among all the treatments, and was superior to pembrolizumab alone (hazard ratio: 0.87; 95% CI: 0.79–0.95). Combination therapy had more grade 3–5 adverse events; but toxicity-related discontinuation and treatment-related death did not increase.Conclusion: Pembrolizumab plus chemotherapy was likely to be the most effective treatment for patients with wild-type advanced NSCLC.